DIVERSITY OF ETHNOBOTANICAL PLANTS USED BY RURAL COMMUNITY OF TRYAMBAKESHWAR HILL OF NASHIK DISTRICT, MAHARASHTRA, INDIA.: Life Science-Botany - V.R.KAKULTE; K.N.GAIKWAD; SMT. S.U.JADHAV (International Journal of Life Science and Pharma Research, 2014)
An ethno botanical survey on medicinal plants and their indigenous uses was carried out in Trymbakeshwar region of Nashik District in Maharashtra. These areas are floristically rich areas where plants of various categories are growing spontaneously in their natural habitat. The rural community of these region uses some of the plants as medicine for the treatment of human ailments. In a floristic survey 31 ethno medicinal plants species belonging to 25 families were recorded from this region. These medicinal plants are listed in alphabetically order of Latin names, local names along with family & part used as medicine